Whether The Provision of Exercises Can Improve Emotional Intelligence - Aini Indriasih; Ngadi Marsinah; Sri Sumiyati (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
This study aims to determine the effectiveness of providing exercises on improving emotional intelligence in early childhood in Pembina Kaliwungu Kindergarten, Kudus regency with a research sample of 2 early childhood groups of 24 each. The research design used is quasi-experimentation by comparing the experimental group and the control group. Data collection uses observation and deed tests. Meanwhile, the data were analyzed with the t-test, which was previously tested for the normality of the data and the homogeneity of the variant. The results of the study obtained an average in the experimental class before being given treatment of 67.25 and the control group of 57.00. Meanwhile, after being given treatment, a score was obtained in the experimental class of 69.33 greater than the average control class of 57.00. Thus there is a difference in average between the experimental class and the control class. The difference test obtained that the average score of the experimental class has increased. the child achieves completeness of learning compared to the control class.